Anthropological Foundations of the Family and the Common Good - Crawford, David S. (Socialinė teorija, empirija, politika ir praktika, 2017)
The family and the common good are often related to each other in contemporarydiscourse and debate, generally in a functionalistic sense: the family is taken to be either necessary or not for the civil common good. However, the family is not itself considered a common good. In fact, however, the family is the paradigmatic example of an “integral common good” because it is the family in which the members are most obviously integrated and related in a community which is in itself a good. Western liberal thought, on the other hand, is unable to conceive the family except in its own image, as a fundamentally constructed reality composed of self-initiating and autonomous individuals. Yet in reality, the family shows us the ontological foundations and meaning of natural human communities, ontological foundations that must be respected and promoted by civil society if it is to be authentically human.